Insights into vertebrate head development: From cranial neural crest to the modelling of neurocristopathies - Weiner, Andrea Maria Julia (2020)
Although the vertebrate head has evolved to a wide collection of adaptive shapes, the fundamental signalling pathways and cellular events that outline the head skeleton have proven to be highly conserved. This conservation suggests that major morphological differences are due to changes in differentiation and morphogenetic programs downstream of a well-maintained developmental prepattern. Here we provide a brief examination of the mechanisms and pathways responsible for vertebrate head development, as well as an overview of the animal models suitable for studying face development. In addition, we describe the criteria for neurocristopathy classifica-tion, highlighting the contribution of zebrafish to the modelling of Treacher Collins/Franceschetti Syndrome, an emblematic neurocristopathy. The contributions from our laboratory reveal that proper zebrafish head development depends on the fine-tuning of developmental-gene expression mediated by nucleic acid binding proteins able to regulate DNA conformation and / or the neuroepithelium redox state.